2021
DOI: 10.1021/acsomega.1c04597
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Cerium Nitrate within Poly(urea-formaldehyde) Microcapsules for the Development of Self-Healing Epoxy-Based Coating

Abstract: In order to study the release of cerium nitrate in a self-healing epoxy-based coating, poly (urea-formaldehyde) (PUF) microcapsules containing cerium nitrate were synthesized. The effects of healing agent concentration and weight percent of microcapsules in the epoxy resin were studied through the incorporation of microcapsules within an epoxy-based coating. The prepared microcapsules were characterized using thermogravimetric analysis and Fourier transform infrared spectroscopy and confirmed the successful en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The EIS measurements were conducted to evaluate the anticorrosion properties of the coatings containing modified and unmodified TiO 2 with respect to the control sample [52] , [53] . Prior to the electrochemical assessment, the samples were scratched and then soaked with a 3.5 wt% NaCl aqueous solution for 18 days to reach a stable open circuit potential.…”
Section: Resultsmentioning
confidence: 99%
“…The EIS measurements were conducted to evaluate the anticorrosion properties of the coatings containing modified and unmodified TiO 2 with respect to the control sample [52] , [53] . Prior to the electrochemical assessment, the samples were scratched and then soaked with a 3.5 wt% NaCl aqueous solution for 18 days to reach a stable open circuit potential.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of compounds such as Ce(NO 3 )6H 2 O and CeO 2 fine powder was also evaluated in the silane chemistry [95,96]. These enhancers, as one calls them in silane sol-gel chemistry, significantly improve the barrier property of sol-gel coatings combined with the anticorrosion properties of cerium ions [97][98][99][100][101][102][103][104][105]. The anticorrosion action of the cerium ions occurs via the passivation of the imperfections or cracks.…”
Section: Inhibitors 61 Inorganicmentioning
confidence: 99%
“…Numerous polymer materials are appropriate for creating the shell of the capsules. The most popular shells for microcapsules formation are poly(urea formaldehyde), [12][13][14][15][16][17] poly(melamine formaldehyde), [18][19][20] poly(urea melamine formaldehyde), 19,21 polyurethane, 22 polyurea, [23][24][25] poly(methyl methacrylate), [26][27][28][29] and others.…”
Section: Introductionmentioning
confidence: 99%
“…15 It was determined, however, that the reaction between the amino groups of PAAE and hydroxyl groups of the melamine-formaldehyde prepolymer occurred during the shell formation leading to reduced size of microcapsules. 16 It was reported that smaller microcapsules were less likely to rupture during the scratch process providing worse self-healing properties to the coating. 15 The successful microencapsulation process depends on numerous controlled and uncontrolled parameters within the preparation process, which are interconnected in a synergistic manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation